Reforming Supervision in State-Owned Insurance Enterprises: Lessons from South Korea - Daniel Kristanto Sitorus; Adi Sulistiyono; Pujiyono Suwadi; Andi Tri Haryono (Contrarius Indonesia, 2026)
Indonesia’s insurance sector continues to expand rapidly, particularly within state owned enterprises managing substantial public funds. However, corruption cases involving PT Asuransi Jiwasraya and PT Asabri exposed weaknesses in corporate governance, regulatory supervision, and institutional coordination that hinder effective prevention of financial misconduct. This study analyzes weaknesses in Indonesia’s current supervisory regime and formulates an anti-corruption supervisory model for state owned insurance companies. The study applies normative legal research through statutory, conceptual, and comparative approaches. The findings reveal that, first, Indonesia’s supervisory system has not established effective risk-based control mechanisms, continuous monitoring systems, or integrated preventive supervision, which consequently weakens the capacity to detect and prevent corruption within state owned insurance companies at an early stage. Second, this study develops a hybrid supervisory model that integrates legal fraud detection, risk-based supervision, early warning mechanisms, legal audits, compliance assessment, administrative veto authority, and preventive involvement of the Attorney General’s Office of the Republic of Indonesia in order to strengthen anti-corruption governance and enhance the protection of public finances.